The Challenges Encountered by EFL Students in Writing Graduation Projects at Tripoli, Gharian and Zawia Universities: Supervisors’ perspectives (Comprehensive Journal of Science, 2026)
This study investigates the challenges encountered by EFL students in writing their graduation projects from supervisors’ perspectives and their attitude towards students’ work. A semi-structured interview was used to collect the qualitative data from 6 supervisors. It was revealed that Libyan students encounter several challenges regarding writing their graduation projects. Academic writing, gathering sources, choosing a topic and insufficient research methodology courses were the most significant challenges thus supervisors have negative attitude towards students’ work. The study also revealed that supervisors play a vital role in overcoming these challenges and they offer some solutions and procedures, such as enhancing both research methodology and academic writing courses.